(untitled) (Research, Society and Development, 2020)
This article aims to describe the epidemiological characteristics of COVID-19 in the state of Bahia, Brazil, during the first quarter of the pandemic, in the year 2020. It is an ecological type study with a descriptive approach, which characterized the pandemic of the COVID-19 in the state of Bahia, Brazil, in the months of March, April and May, in the year 2020. Epidemiological data were obtained from the Epidemiological Bulletin COVID-19 BAHIA, provided by the Epidemiological Surveillance Directorate of the State Health Department of Bahia, arising from the notifications made by the health secretariats of the 417 municipalities of that state. Of the total confirmed cases (18,392) according to the criteria indicated above, the total number of health professionals affected by the disease was 2,683, equivalent to 14.58%. The five groups of professionals most affected in the state were: auxiliary and nursing technician (890); nurse (555); physician (312); physical therapist (96); social worker (56). The other professionals together added up to 774 confirmed cases. As for the sex of confirmed cases, 53.01% were female, 44.08% were male. The most affected age group was 30 to 39 years old. Regarding deaths by municipality of residence in the state of Bahia, 667 deaths by COVID-19 were found, with a lethality coefficient of 3.63%. It was found that the capital of Bahia led the number of cases and deaths by COVID-19, that the female sex led the number of cases and the male the highest percentage of death. Adults were the most affected, especially when they had some associated comorbidity.